GAMBARAN KEBUGARAN KARDIORESPIRATORI, STATUS GIZI DAN KADAR HEMOGLOBIH PEKERJA SAWIT DI PT. INTI MELIA PELINDO - Deni Sintia; Arif Fadli Muchlis; wilda welis; Septri; sonya nelson; Fahmil Haris (Jurnal IKEOR, 2023)
The purpose of this study was to improve the description of cardiorespiratory fitness, nutritional status and hemoglobin levels of palm oil administration and field workers at PT. Melia Inti Pelindo, South Solok Regency. This type of research is descriptive. The population in this study were 27 people consisting of 11 administrative workers and 16 field workers. The sampling technique used is total sampling, by making the entire population a research sample. Data was collected using the Harvard step test, height and weight and measurement of hemoglobin. The data in this study are processed using the percentage formula. The results of research that researchers have done some time ago, gave the following results: (1) Cardiorespiratory fitness of administration and field workers at PT. Melia Inti Pelindo, South Solok Regency, is in the "Bad" classification. (2) The nutritional status of administrative and field workers at PT. Melia Inti Pelindo, South Solok Regency, is in the “Normal” classification. (3) Hemoglobin level of administration and field workers at PT. Melia Inti Pelindo, South Solok Regency, is classified as “Normal”